Obstetrical Outcomes in Primigravida with Engaged Versus Unengaged Fetal Head during Spontaneous Labor: Outcomes in Primigravida - Lutfullah, Zunaira; Mustafa, Nilofer; Aslam, Pakeeza; Mushtaq, Qurratulain; Samreen, Seema; Salik, Neha; Maqbool, Sania (Pakistan Journal of Health Sciences, 2024)
When the fetal head’s widest diameter fits into the pelvic inlet, it is referred to as engaged. When a primigravida’s labor begins with the fetal head still not engaged, she was most likely to experience an obstructed labor. This study was conducted at a large tertiary care center with adequate sample size to determine the study outcomes. Objective: To compare the obstetrical outcomes in primigravida with engaged versus unengaged fetal head at the onset of spontaneous labor in terms of delivery methods and associated risks. Methods: This was a case control study. Study was conducted at Department of Obstetrics and Gynecology National Hospital Defence, Lahore. One hundred thirty patients through non-probability consecutive sampling. Demographic data like name, age was recorded for participants. Data were analyzed using SPSS version 22.0. RR was calculated for two groups. Results: Mean age of patients was 22.4 ± 2.6 years. Total 44.7% patients had C-section. When comparison of engaged and unengaged fetal head, 49 patients out of 88 i.e. 55.68% patients had engagement of head in vaginal delivery group and 16 patients out of 42 i.e. 38% patients had engagement of fetal head in C-section group. Relative risk among two group was 1.2564 and z score was 1.847 and p value was 0.0648. Conclusion: Relative risk of primigravida getting C-section was high with un- engaged fetal head compared to primigravida who has engaged fetal head